Oil and Gas Export Value Analysis and the Economy Indonesia Period 2010-2021 - Mayesti, Indria; Afrizal, Ardi; Neldawaty, Rika; Halim, Abd. (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of the first research is on the development of the value of oil and gas exports in Indonesia during the 2010-2021 period for the last 12 years where the average value of Indonesia's oil and gas exports is 22,171 (000 US$) or a decline of up to an average of 2.18% per year. The highest oil and gas export occurred in 2011 which was 41,477 (000 US$) or grew by 47.92%, while the lowest oil and gas export condition occurred in 2015 which was 18,574 (000 US$) or decreased by 38.12%. The second research objective uses a regression model of the effect of the value of oil and gas exports on economic growth in Indonesia during the period 2010-2021 with a partial constant value of the X1 variable (oil and gas exports) having a significant effect of 0.005 with a constant value of 116.87 meaning that if oil and gas exports increase by 1% then Economic growth also increases and vice versa. Furthermore, the influence of these variables is also shown from the R Square determination test, which is 77.50%, meaning that in general this study found that during this research period, it was actually not recommended for Indonesia to export oil and gas abroad because it involved the sufficiency of domestic oil and gas needs.